Risk factors for low birth-weight in areas with varying malaria transmission in Korogwe, Tanzania: implications for malaria control - Mmbando, BP; Cole-Lewis, H; Sembuche, S; Kamugisha, ML; Theander, T; Lusingu, JPA; Lemnge, MM (Tanzania Journal of Health Research, 2008)
Low birth weight (LBW) is a risk factor for infant mortality, morbidity, growth retardation, poor cognitive development, and chronic diseases. Maternal exposure to diseases such as malaria, HIV, and syphilis has been shown to have a significant impact on birth weight (BW). This study was aimed at determining whether there was a difference in rates of LBW in areas of varying malaria transmission intensity in Korogwe, Tanzania.Retrospective data for one year (June 2004-May 2005) in three maternal and child health (MCH) clinics in the district were analysed. Villages were stratified into three strata: lowlands-semi urban (average altitude of 320m), lowlands-rural (below 600m) and highlands (≥600m). There was a significant decreasing trend of rate of LBW from rural lowlands to highlands (χ2 trend =7.335, P=0.007). Adjusting for covariates, women in parity-two were at reduced risk of delivering LBW babies compared to first parity women (OR=0.44, 95% CI 0.19-0.98, P=0.045). Similarly, the risk of LBW was higher in women who had delayed MCH gestational booking and in women who conceived during high malaria transmission seasons. There was high degree of preference of digits ending with0/5 in reporting BW in the studied MCHs. In conclusion, a rate of LWB was high in rural lowlands where malaria is also endemic, and was associated with high malaria transmission seasons. Keywords: Low birth weight, malaria, transmission intensity, Tanzania Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 137-143